TOKEN REINFORCEMENT, COGNITIVE BEHAVIOURAL THERAPY, DEGREE OF DISABILITY AND MANAGING AGGRESSIVE BEHAVIOUR AMONG PUPILS WITH INTELLECTUAL DISABILITY - Jacob, Udeme Samuel; Pillay, Jace; Adegboye, Kehinde (Jurnal Tatsqif, 2022)
Aggressive behaviour has a significant negative effect on learning and academic performance. This study investigated the significant main effect of token reinforcement, cognitive behavioural therapy, and degree of disability on managing aggressive behaviour among pupils with intellectual disability. The study participants were 60 pupils (N = 60, N = 27 boys; N = 33 girls; mean age = 11.7) with intellectual disability who were purposively selected from three (3) special schools in Ibadan Metropolis. The participants were divided into three treatment groups: token reinforcement, cognitive behavioural therapy, and control groups, with the degree of disability as the moderating factor. The token reinforcement and cognitive behavioural therapy groups met for thirty sessions over twelve weeks. Two treatment groups were assessed using the Overt Aggression Scale, while the three treatment groups were assessed post-intervention using the Overt Aggression Scale. Data for aggressive behaviour performance were collected after the participants were screened for mild intellectual disability. An analysis of covariance and estimated means was used to examine the data. The results revealed a statistically significant difference between the pre-test and post-test results of the three (3) treatment groups. The degree of disability on the aggressive behaviour of pupils with mild intellectual disability was significant. The interaction effect of treatment and degree of disability was significant on participants' aggressive behaviour. Based on this study's findings, the recommendation is that token reinforcement and cognitive behavioural therapy be adopted to manage aggressive behaviour among pupils with mild intellectual disability.